Analisis Dialek Lokal Sebagai Penanda Identitas Lokal Individu ( Studiinterlanguage Mahasiswa Di Ilmu Administrasi Negara Stisospol â€œWaskita Dharmaâ€ Malang) - Syakur, Abdul (JAMAK, 2014)
An analysis of Dialect is the symbol of individual an identity From the dialect, every individual did not understand but they have undrestood, in another hands the presence of glowing present dialect phenomena in the stu dent circles, the identity of every individual becomes disguised. The students would rather feel more comfortable to use the present dialect than local dialect. They do this to mak e the process of social adaptation and adjustment easily. This reserach has an objective in observing communication experience and understanding of students in using interlanguage for social and comunication directly in Stisospol â€œWask ita Dharmaâ€ Malang The result of this research shows that the students would rather choose to use the present dialect to be able to adapt and communicate with the surroundings and another student in Stisospol â€œWask ita Dharmaâ€ Malang the present dialect which is used by the students constituties the adaptation process with new surroundings. They can jo in into a new group if they use the same dialect which is considered as superior dialect. Although the informan would rather choose to use the present dialect than their own local dialect, they still have an understanding about the existence of local dialect. Dialect is one of our own national culture, so if we do not perpetuate that our local dialect can be extinct. Key word:Interlanguange, present dialect, local dialect, students Style in accent.